The first power spectrum limit on the 21-cm signal of neutral hydrogen during the Cosmic Dawn at z = 20–25 from LOFAR. Issue 3 (12th July 2019) - Gehlot, B K; Mertens, F G; Koopmans, L V E; Brentjens, M A; Zaroubi, S; Ciardi, B; Ghosh, A; Hatef, M; Iliev, I T; Jelić, V; Kooistra, R; Krause, F; et al.
ABSTRACT: Observations of the redshifted 21-cm hyperfine line of neutral hydrogen from early phases of the Universe such as Cosmic Dawn and the Epoch of Reionization promise to open a new window onto the early formation of stars and galaxies. We present the first upper limits on the power spectrum of redshifted 21-cm brightness temperature fluctuations in the redshift range z = 19.8–25.2 (54–68 MHz frequency range) using 14 h of data obtained with the LOFAR-Low Band Antenna (LBA) array. We also demonstrate the application of a multiple pointing calibration technique to calibrate the LOFAR-LBA dual-pointing observations centred on the North Celestial Pole and the radio galaxy 3C220.3. We observe an unexplained excess of 30\!-\!50 per cent in Stokes / noise compared to Stokes V for the two observed fields, which decorrelates on ≳12 s and might have a physical origin. We show that enforcing smoothness of gain errors along frequency direction during calibration reduces the additional variance in Stokes I compared Stokes V introduced by the calibration on sub-band level. After subtraction of smooth foregrounds, we achieve a 2σ upper limit on the 21-cm power spectrum of Δ _21^2 (14561 mK)^2 at k0.038 h cMpc^-1 and Δ _21^2 (14886 mK)^2 at k0.038 h cMpc^-1 for the 3C220 and NCP fields respectively and both upper limits are consistent with each other. The upper limits for the two fields are still dominated by systematics on most k modes.